2014
DOI: 10.1186/1757-2215-7-16
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin pathway as a potential prognostic and predictive marker in patients with advanced ovarian cancer

Abstract: Backgroundβ-catenin is the key protein in the WNT signalling pathway and it forms adherent junctions together with E-cadherin. In ovarian carcinoma, abnormal expression of β-catenin, E-cadherin and WNT-1 was observed, but their prognostic and predictive role is unclear. The aim of this study was to clarify the prognostic and predictive role of E-cadherin, β-catenin and WNT-1 in advanced epithelial ovarian carcinoma (AEOC).MethodsThe expression of E-cadherin, β-catenin and WNT-1 was determined by immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 51 publications
8
61
1
Order By: Relevance
“…Various signaling pathways have been implicated in gonadotropin-induced proliferation, invasion, and metastasis formation in ovarian cancer, such as the RAS/RAF/ MAPK/ERK (Pilarski et al 2012, Hilliard et al 2013, Smolle et al 2013, PI3K/PTEN/AKT/mTOR (Cancer Genome Atlas Research Network 2011, Huang et al 2011, Yamamoto et al 2011, 2012, Carden et al 2012, Abe et al 2013, Dobbin & Landen 2013, and Wnt/ b-catenin signaling pathways (Bodnar et al 2014, Ford et al 2014, Qi et al 2014. Gonadotropin (FSH and LH) receptors share various downstream signaling pathways, including PI3K and MAPK, and consequently, the potential crosstalk between gonadotropins and molecular pathway signaling is of great interest in exploring targeted cancer therapies.…”
Section: Treatments Targeting Downstream Results Of Endocrine Influencesmentioning
confidence: 99%
“…Various signaling pathways have been implicated in gonadotropin-induced proliferation, invasion, and metastasis formation in ovarian cancer, such as the RAS/RAF/ MAPK/ERK (Pilarski et al 2012, Hilliard et al 2013, Smolle et al 2013, PI3K/PTEN/AKT/mTOR (Cancer Genome Atlas Research Network 2011, Huang et al 2011, Yamamoto et al 2011, 2012, Carden et al 2012, Abe et al 2013, Dobbin & Landen 2013, and Wnt/ b-catenin signaling pathways (Bodnar et al 2014, Ford et al 2014, Qi et al 2014. Gonadotropin (FSH and LH) receptors share various downstream signaling pathways, including PI3K and MAPK, and consequently, the potential crosstalk between gonadotropins and molecular pathway signaling is of great interest in exploring targeted cancer therapies.…”
Section: Treatments Targeting Downstream Results Of Endocrine Influencesmentioning
confidence: 99%
“…However, the role of the Wnt pathway in the various OC subtypes remains undefined, partly because of its diverse mechanisms of activation in OC [8]. Indeed, bcatenin mutation is mainly confined to endometrioid adenocarcinomas [9] where it is predominantly expressed in the nucleus; it is at the "heart" of the Wnt/b-catenin pathway and activates the expression of many important proteins responsible for the cell cycle, proliferation, and survival, such as cyclin D1 and c-myc [10].…”
Section: Introductionmentioning
confidence: 99%
“…β-catenin forms adherent junction together with E-cadherin. Most of patients (87.5 %) with objective response had decreased membrane β-catenin expression, and that was statistically significant [34].…”
Section: Discussionmentioning
confidence: 88%
“…In his meta-analysis, Peng et al found that cut off ≥ 10 % was used in most of the published studies [27][28][29][30][31][32][33][34].…”
Section: Immunohistochemical Staining and Analysismentioning
confidence: 97%